Clitics in Slovak with(out) constraints. Corpus frequency versus acceptability ratings (Jazykovedný časopis, 2025)
Using data from a representative corpus of Slovak and an acceptability survey, the preferential placement of clitic components in object clause constructions in Slovak have been investigated. Slovak clitics are usually described as elements following Wackernagel’s Law and belonging to the category of second-position clitics. However, usage-based investigations show that their placement varies within a clause, depending on various pragmatic and syntactic factors and a set of constraints which limit their movement within the clause structure. By comparing data from corpus analysis and acceptability ratings by native speakers, it is shown how judgments and actual usage of clitics may converge or diverge in particular cases.